(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2025)
The management of Tetralogy of Fallot (TOF), one of the commonest congenital anomalies, has advanced rapidly and excellent long-term survival were observed. Residual defects like pulmonary valve regurgitations are identified in an increased number as long-term survival increased and requirement for intervention increased worldwide. Although rare in our setting, we performed aortic valve replacement (AVR) with re-do pulmonary valve replacement surgery on a 21-year-old, non-diabetic, hypertensive young male with the diagnosis of moderate to severe aortic regurgitation with stuck pulmonary (mechanical) valve, with status-post intracardiac repair (ICR) for Tetralogy of Fallot (TOF) with aortic valve repair (AVRe) with pulmonary valve replacement (PVR) with closure of ventricular septal defect (VSD). His postoperative recovery was satisfactory and he was discharged symptom free on 6th postoperative day. J Bangladesh Coll Phys Surg 2024; 306: 306-309